Developing the university in Ukhta: an arctic turn - Nikolay D. Tshadaya (Высшее образование в России)
During the fifty five years Ukhta State Technical Univers ity has accumulated the considerable experience in training highly skilled personnel for the gas and oil industry. The article focuses on the creation of innovative territorial cluster «Oil and gas technologies» on the basis of USTU and the university participation in realization of Russia’s Arctic strategy